Investigation of high risk area affected by electromagnetic field [EMF] radiation from high voltage power transmission lines / Nor Fatin Ismail - Ismail, Nor Fatin Ismail (2019)
Since centuries ago, the creation of electricity has given many advantages and conveniences to humans. However, it gives side effects that arise from the use of electricity itself. The increasing of electricity consumption give an impact to human and environment because of electromagnetic field that produces when the electric passes an object. This field emits radiation which resulted in increasing of temperature in the atmosphere. The main objective of this study is to analyse electromagnetic field (EMF) radiation impact from high voltage power transmission line in Kedah state. Electrical substation line, Landsat image year 2011, 2014 and 2016 land used of study area were used to investigate the affected area. The most affected area by EMR radiation is agriculture area followed by forest area. The increasing effect of EMR on residential area is 0.7% in year 2011. The significant for this study help the government agencies to evaluate the pollution that has occurred in the atmosphere throughout six year intervals.